Mitigasi Bencana Berbasis Kearifan Lokal di Daerah Wadaslintang Kabupaten Wonosobo - Fahrus Widodo; Suwarno Suwarno (UM Purwokerto Press, 2022)
This research is about the mitigation or prevention of social disasters based on local wisdom that occurred in the Wadaslintang area, Wonosobo Regency. This study uses a qualitative approach. Data were collected through this research method using the method of literature study or literature study. This method was chosen because of the short research time and to find references on the basis of theories that are relevant to the cases or problems found. This study aims to determine one of the local wisdoms used to prevent social disasters. The results showed that: (a). The slamatan (tumpengan) which is given the name buceng stands for